The NovoStent®® SAMBA®® stent: a novel alternating helix self-expanding nitinol stent design. (April 2011) - Zeller, Thomas; Brääunlich, Sven; Waldo, Michael; Cheng, Christopher; Macharzina, Roland; Scheinert, Dierk; Rastan, Aljoscha
Technical and clinical outcomes of femoro––popliteal artery stenting are highly dependent on stent design properties. First-generation slotted-tube nitinol stents did not sufficiently address the unique mechanical stress applied to this vessel segment resulting in high stent fracture rates that have been linked to restenosis. The main advantage of slotted-tube stents is their clinical ease of use. Changing their design from ringed to helical axial connections resulted in improved flexibility with minimal impact to compression resistance. However, specific design properties of traditional slotted-tube stents such as metallic vessel wall coverage, chronic radial outward force and blood flow modulation do not sufficiently address the need to reduce excessive restenosis rates. The NovoStent ®® SAMBA ®® stent represents a new generation nitinol stent design basically consisting of an alternating helix offering unique properties in terms of flexibility, compression resistance, vessel-wall coverage and a very low chronic outward force. We evaluate the NovoStent SAMBA stent in a peripheral animal model and compare bench mechanical performance to established slotted-tube stent designs. A clinical study is currently underway.